Bilateral tonic pupil during a migraine attack: a case report. - Storarri, Ana Carolina Montouro; Higa Lee, Annelise Akemi; Renan, Domingues (Headache Medicine, 2024)
Tonic pupil or Adie’s pupil occurs due to parasympathetic denervation, and it is characterized by mydriasis with little or no response to light, with pupillary contraction to accommodation. It is caused by eye pathologies, such as infections, trauma, neoplasms, inflammatory diseases, and systemic diseases with autonomic dysfunction. Few cases have been reported of bilateral tonic pupils associated with migraine attacks. Our aimed to describe the case of a young female patient with a history of chronic migraine without aura, who presented acutely with bilateral pupillary mydriasis during a migraine attack, characterized as tonic pupil, and to discuss the possible causes of mydriasis during a migraine attack.